Databases and web resources for neglected tropical disease research - Praffulla Kumar Arya, Krishnendu Barik, Ajay Kumar Singh, Anil Kumar (Journal of Applied Pharmaceutical Science, 2023)
The term “neglected tropical diseases” (NTDs) refers to a group of infectious diseases that are common in developing tropical and subtropical nations. There are 20 such diseases that are prevalent in 149 countries according to the World Health Organization. These diseases have a devastating impact on the economies of affected countries and result in enormous losses in terms of morbidity and mortality. All NTDs need to receive more attention to prevent widespread epidemics and outbreaks that could result in a high death toll globally. The few drugs that are already on the market are no longer effective against many infectious diseases, and various other problems, such as toxicity and pharmacokinetics concerns, also prohibit the eradication of these diseases. One of the crucial steps in the drug discovery pipeline is the identification and validation of a therapeutic target based on the biology of the organism. This review provides an overview of more than 35 web-accessible NTD databases categorized under general, specialized, and other NTD databases and highlights recent advances. These databases can be very useful for research, especially drug design and discovery against NTDs. The majority of these databases are simple to use and freely accessible online.
Keywords: Neglected tropical diseases, infectious diseases, therapeutic target, drug discovery